2020
DOI: 10.4314/ejhs.v30i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Stress and Associated Factors among Academic Staffs at the University of Gondar, Northwest Ethiopia: An Institutionbased Cross-sectional Study

Abstract: BACKGROUND: Work-related stress is described as a physiological and psychological reaction to the harmful aspects of workplace content. Current evidence indicates that the world of education is a highly stressful occupation. However, in academicians in sub-Saharan African countries, such as Ethiopia,the prevalence and contributing factors are not well studied. This study was, therefore, aimed at filling this gap.METHODS: A cross-sectional study was conducted from March to April 2018. Stratified sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…A study conducted among academic staff in Gondar University, Ethiopia, found the prevalence of work-related stress to be 60.4%. This study also found smoking, high job demand, low job control and age as significant factors affecting stress 19 . Studies conducted in several universities of Nigeria have found very high stress levels among university lecturers 20,21 .…”
Section: Introductionsupporting
confidence: 57%
“…A study conducted among academic staff in Gondar University, Ethiopia, found the prevalence of work-related stress to be 60.4%. This study also found smoking, high job demand, low job control and age as significant factors affecting stress 19 . Studies conducted in several universities of Nigeria have found very high stress levels among university lecturers 20,21 .…”
Section: Introductionsupporting
confidence: 57%
“…Currently, the University has 5 campuses: the College of Medicine and Health Sciences and Comprehensive Specialized Hospital (CMHS), Maraki, Atse Tewdros, Atse Fasil, and Teda. 38 During the study period, there were a total of 2858 academic staff on all campuses.…”
Section: Methodsmentioning
confidence: 99%
“…Soetan (2018) found that in a population of lecturers in South Western Nigeria, high-stress level is prevalent. Based on current evidence, the world of education is highly associated with stressful conditions which account for about 60.4% prevalence of work-related stress (Kabito et al, 2020). Most of university lecturers experience a lot of stress as a result of too much usage of technology to solve students' academic problems (Du Plessis, 2019).…”
mentioning
confidence: 99%